Interações entre o estresse repetido e clomipramina: diferentes respostas em ratos machos e fêmeas - Balk, Rodrigo de Souza (2011)
Repeated stress or stressful events has been reported to induce anxiety and depression. Differential responses to repeated stress and antidepressant treatments have been observed in males and females. Clomipramine is a tricyclic antidepressant that inhibits the reuptake of serotonin and norepinephrine by indirect actions on the dopaminergic system and limbic-hypothalamic-pituitary-adrenal (LHHA) axis. Its chronic use increases the body's ability to cope with stress; however, high doses can potentiate its side effects on memory, learning, and sensory motor function. Thus, this study investigated sexrelated differential response to repeated restraint stress and chronic administration of clomipramine on parameters of oxidative stress in cerebral cortex, hippocampus and striatum (Manuscript 1) and behavior in rats (Manuscript 1). Male and female rats were divided into control and repeated restraint stress, and subdivided into treated or not with clomipramine during 40 days of stress and 27 days of clomipramine treatment (30mg/kg). The model of repeated restraint stress used in this study increased oxidative damage particularly in striatum and hippocampus of females in higher sensitivity to stress compared to males (Manuscript 1). In this context, the levels of non-enzymatic antioxidant such as the levels of non-protein thiol (NP-SH), and enzymatic antioxidants such as the enzyme superoxide dismutase (SOD), catalase (CAT) and Na+/ K+-ATPase (Manuscript 1) also changed in both sexes. Antidepressant treatment with clomipramine increased the oxidative damage caused by the imbalance between oxidants/antioxidants, particularly in males. Regarding the behavioral activities (Manuscript 1), females subjected to repeated restraint stress had higher anxiety and lower motivation when compared to males. On the other hand, males had impaired non-spatial memory formation through variables such as the short and long term memory as well as a reduction in exploratory and locomotor activity compared to females. Sex differences were also checked as to which antidepressant treatment that potentiate the deficits on the non-spatial memory formation, locomotor and exploratory activities and motivation in males, but in contrast was observed an increase in anxiety and a reduction on the consumption of sweet food in females. Finally, the results of this study indicate that females are particularly sensitive to stress on anxiety and motivation while males on the spatial memory formation as well as locomotor and exploratory acitvities. Antidepressant treatment with clomipramine appears to have neuroprotective effect in females, but cytotoxic in males in what might be observed by the increase in the neurochemical and behavioral deficits.